ANALISIS FAKTOR-FAKTOR FUNDAMENTAL PERUSAHAAN YANG MEMPENGARUHI HARGA SAHAM (Studi Kasus Pada Perusahaan LQ45 Yang Terdaftar Di BEI Periode 2009-2011) (Students' Journal of Accounting and Banking, 2014)
This research aim to to know the influence Earning Per Share ( EPS), Return On Equity ( ROE), Net Profit Margin ( NPM), and Current Ratio (CR) either through parsial and simultan to share price at company Indeks LQ45 which enlisted in BEI. Period of research started from year of 2009-2011 ( 3 year). Method analyse the data use the assumption test classical, analyse regresi doubled and examination of hypothesis. Research result indicate that the variable Earning Per Share (EPS) and Return On Equity (ROE) have an effect on to share price parsially is while Net Profit Margin (NPM) and Current Ratio (CR) don't have an effect on to share price. To the finance ratio consisting of EPS, ROE, NPM, ROE, and CR influential togetherly to share price is in the year 2009-2011.Keywords: Share Price, Earning Per Share (EPS), Return On Equity (ROE), Net Profit Margin (NPM), and Current Ratio (CR)